ETNOMATEMATIKA DALAM AKTIVITAS PENDISTRIBUSIAN BARANG OLEH PEDAGANG ONLINE - Nelisa Nelisa; Asep Nursangaji; Silvia Sayu; Dona Fitriawan; Rustam Rustam; Munaldus Munaldus (IKIP Siliwangi, 2023)
Mathematics that is done in everyday life which functions to facilitate work, transactions and so on is called ethnomathematics. This study aims to describe ethnomathematics in goods distribution activities carried out by online traders. The approach used is a qualitative approach. The number of research subjects was 4 online traders consisting of 2 agents and 2 resellers. The research location is in Sungai Kelambu Village, Tebas District, Sambas Regency. The research was carried out on March 20 and March 25, 2022. Data collection techniques used observation, interviews and documentation. The research procedure was carried out in 4 stages, namely the pre-research stage, data collection, data analysis and report preparation. The research instruments were observation sheets, interview guides, and documentation. The results of the study show that there is ethnomathematics in the distribution of goods carried out by online traders. The ethnomathematical activities in the distribution of goods can be seen in the materials on measurement, assemblage, number arithmetic operations, comparisons, least common multiples (KPK), and social arithmetic.